2008
DOI: 10.1080/15421400801904369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urea Concentration and Vacuum Treatment on Physical and Mechanical Properties of Methyl Metacrylate Bamboo

Abstract: Betung bamboo (Dendrocalamus asper) samples were obtained from Bogor area, Indonesia. The samples were air dried, and then immersed into methyl metacrylate-urea solution for 24 hours prior to irradiation. Urea was added into methyl metacrylate (MMA) with concentration of 1%, 3%, and 5%, and without urea as control. The samples were vacuumed at 35 mmHg for five minutes prior to immersion, and without vacuum were done as well as control. The samples were wrapped up with aluminum foil and then with polyvinyl shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The results of polymer loading with the impregnation process were better than those obtained by Hadi et al (2008). In that study, betung bamboo (Dendrocalamus asper) was impregnated with MMA and radiated with 60…”
Section: Physical Propertiesmentioning
confidence: 88%
“…The results of polymer loading with the impregnation process were better than those obtained by Hadi et al (2008). In that study, betung bamboo (Dendrocalamus asper) was impregnated with MMA and radiated with 60…”
Section: Physical Propertiesmentioning
confidence: 88%
“…Klüppel et al (2015) concluded that higher polymer loading of impregnating resin and a higher percentage weight gain from acetylation or furfuryl alcohol impregnation of wood increased resistance to biodeterioration attack. Hadi et al (2008) reported that MMA-impregnated bamboo had much better physical and mechanical properties than untreated bamboo. In another study, Hadi et al (2013) impregnated jabon wood with MMA and obtained an average polymer loading 34%.…”
Section: Introductionmentioning
confidence: 99%